Validating the Essen Climate Evaluation Schema modified for people with learning disabilities in a low‐risk secure forensic setting. (12th November 2020) - Barker, Lindsie; McKeown, Annette; Small, Michelle; Meggs, Jenny
Abstract: Background: Research has shown that an empowering and nurturing yet challenging work climate is beneficial for people receiving clinical services as it increases patient satisfaction, motivation, engagement, therapeutic alliance and functional improvement. Therefore, for inpatients, monitoring, encouraging and understanding ward climate holds considerable potential for improving forensic mental health services. To date, the most widely employed tool for ward‐climate, the Essen Climate Evaluation Schema (EssenCES), has been evidenced as useful in medium and high security hospitals, but little tested with people with learning disabilities or in low security services. Aims: To establish the internal consistency and factor validity of the EssenCES, modified for easier reading, in a low secure hospital unit for people with learning disabilities. Method: Language in the EssenCES was simplified and picture supplements added to facilitate comprehension. Patients completed the scale as part of their clinical routine, supported by National Health Service (NHS) employed psychology assistants. The research team, entirely independent of NHS staff, extracted data from the electronic records of purposively sampled residents in a low‐secure forensic hospital setting for people with learning disabilities. Findings: Two hundred and twenty‐seven records (70% men) were acquired. The EssenCES was shown to have good factor validity and retained the original three factor model including the subscales: therapeutic hold, safety and cohesion . One single‐item from the ' therapeutic hold' subscale was removed to improve the internal consistency ( p < 0.05). Conclusions: This study adds preliminary support for the use of the EssenCES (with removal of one item) in individuals with learning disabilities within low‐risk secure forensic hospital settings.